INDEKS KEKERINGAN SPI (STANDARDIZED PRECIPITATION INDEX) DAN PENGARUHNYA TERHADAP PRODUKTIVITAS HORTIKULTURA TAHUNAN DI KABUPATEN JEMBER - Arzaky Ardi Surya Nugroho; Cahyoadi Bowo; Joko Sudibya (Berkala Ilmiah Pertanian, 2019)
ABSTRACT Perennial tropical horticulture is a superior product whose productivity is affected by water availability. The impact of climate fluctuations due to global warming affects the availability of ground water. This study aims to determine the effect of the Standardized Precipitation Index (SPI) drought index derived from rainfall data on the productivity of perennial horticulture (durian, avocado and rambutan). The study was conducted from July 2016 - November 2018 in 9 sub-districts in Jember Regency where has the highest production. Rainfall data is proceed into SPI data according to the guidelines of the WMO (World Meteorological Organization). Productivity data derived from production data divided by the number of plants. The results of 12 monthly SPI calculations compared with the perennial horticultural productivity data. To find out the relationship between productivity and SPI, the correlation method is used. The results showed that the appropriate SPI value for observing annual horticultural productivity was SPI 9 and 12 monthly. The value of SPI greatly influences the correlation of productivity of durian, avocado and rambutan. Keywords: SPI, productivity, annual horticulture. ABSTRAK Tanaman hortikultura tropis tahunan adalah produk unggulan yang produktivitasnya dipengaruhi oleh ketersediaan air. Dampak fluktuasi iklim akibat pemanasan global mempengaruhi ketersediaan air tanah. Penelitian ini bertujuan untuk mengetahui pengaruh index kekeringan SPI yang berasal dari data curah hujan terhadap produktivitas hotikultura tahunan (durian, alpukat dan rambutan). Penelitian dilakukan mulai bulan Juli 2016 – November 2018 pada 9 Kecamatan dengan produksi tertinggi di Kabupaten Jember. Data curah hujan diolah menjadi data SPI sesuai pedoman WMO (World Meteorological Organization) dan data produktivitas berasal dari data produksi dibagi jumlah tanaman kemudian hasil perhitungan SPI 12 bulanan dibandingkan dengan data produktifitas hortikultura t ahunan. Untuk mengetahui hubungan produktivitas dan SPI digunkan metode korelasi. Hasil penelitian menunjukkan nilai SPI yang sesuai untuk mengamati produktivitas hortikultura tahunan adalah SPI 9 dan 12 bulanan. Nilai SPI sangat berpengaruh terhadap korelasi produktivitas durian, alpukat dan rambutan. Nilai SPI yang semakin tinggi menaikkan produktivitas durian, tetapi menurunkan produktivitas alpukat dan rambutan. Kata Kunci : SPI, produktifitas, hortikuktura tahunan